Carbon Nanotube and Graphene-Reinforced Vegetable Oil-Based Nanocomposites - Abul, Hasnat; Abdul, Moheman; Mohd Amil, Usmani; Showkat, Ahmad Bhawani; Khalid Mohammed, Alotaibi (Springer, 2024)
Natural renewable resources are increasingly being used in the synthesis of innovative polymeric materials due to their diverse features and eco-friendliness. Among them, vegetable oil is widely available and relatively inexpensive throughout the world. Numerous polymeric materials have been developed using vegetable oil as the starting material. These materials have received prominent applications in the diverse elds of biomedical, bioengineering, and other industrial arenas. Several medications have been performed in order to augment applications with advanced materials, such as the incorporation of metals, metalloids, organic moieties, grafting of suitable materials, and blending with other polymeric materials. The addition of a small fraction of nanomaterial to polymers has been found to signicantly increase the performance of pristine polymers. The purpose of this chapter is to provide an overview of some important vegetable oil-based polymer nanocomposites using graphene and carbon nanotubes and their derivatives as reinforcement materials.